Developments in the global hydrogen market: Electrolyser deployment rationale and renewable hydrogen strategies and policies. Issue 10 (October 2020) - Newborough, Marcus; Cooley, Graham
Abstract : This article explores the importance of renewable hydrogen in achieving a 'climate neutral' energy system, which will require a large amount of renewable electricity and a very large amount of renewable hydrogen. Because of the fundamental need for energy storage to match supply and demand, a two-carrier approach needs to be adopted, where both electricity and hydrogen are derived from renewable energy. National hydrogen strategies, electrolyser deployment plans and the actions required by governments to overcome the current policy vacuum are discussed. It is recommended that a cross-sector 'green electrons and green molecules' strategy is taken, and that policies are developed urgently for advancing the adoption of renewable hydrogen.